2016
DOI: 10.3109/13816810.2015.1039139
|View full text |Cite
|
Sign up to set email alerts
|

Duane retraction syndrome in a patient with Duchenne muscular dystrophy

Abstract: This boy is the third patient to be reported with DRS and DMD, the second with bilateral DRS and the only one with other neurologic features. Mutated dystrophin is present in extraocular muscles and in the central nervous system (CNS) in DMD, leaving open the question of whether this co-occurrence is the result of the genetic muscle abnormality, CNS effects caused by dystrophin mutations, or chance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This is the first report to describe the presence of a heterozygous mutation or deletion of the dystrophin gene in a female patient with DRS. However, the coincidence of DRS with dystrophin mutations in the setting of males with Duchenne muscular dystrophy has been described three times previously, including a recent report by our group describing a boy with bilateral DRS, unequivocal DMD, and a small X chromosome duplication involving exons 3 and 4 of the dystrophin gene 3 . These three patients imply a possible association between dystrophin gene changes and DRS that has not yet been evaluated in a larger group of patients with nonsyndromic or syndromic DRS.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This is the first report to describe the presence of a heterozygous mutation or deletion of the dystrophin gene in a female patient with DRS. However, the coincidence of DRS with dystrophin mutations in the setting of males with Duchenne muscular dystrophy has been described three times previously, including a recent report by our group describing a boy with bilateral DRS, unequivocal DMD, and a small X chromosome duplication involving exons 3 and 4 of the dystrophin gene 3 . These three patients imply a possible association between dystrophin gene changes and DRS that has not yet been evaluated in a larger group of patients with nonsyndromic or syndromic DRS.…”
mentioning
confidence: 88%
“…However, the coincidence of DRS with dystrophin mutations in the setting of males with Duchenne muscular dystrophy has been described three times previously, including a recent report by our group describing a boy with bilateral DRS, unequivocal DMD, and a small X chromosome duplication involving exons 3 and 4 of the dystrophin gene. 3 These three patients imply a possible association between dystrophin gene changes and DRS that has not yet been evaluated in a larger group of patients with nonsyndromic or syndromic DRS. Interestingly, single nucleotide polymorphisms in the dystrophin gene have been found in association with oral clefts, 4 creating a potential association between mutated dystrophin and facial clefts that are at times also associated with congenital abnormalities of ocular alignment and motility.…”
mentioning
confidence: 99%
“…Shrestha et al [10] reported a case of Goldenhar syndrome with DRS in a 8month old child. Miller et al [11] presented the association of DRS with craniofacial malformations, Bosley et al [12] reported a case of bilateral DRS with Duchenne muscular dystrophy. Jethani et al reported a case of DRS with Bardet-Biedel syndrome in a 7yr old child.Kawano et al [13] reported a case of DRS with Morning glory syndrome in a 9yr old child.…”
Section: Case Reportmentioning
confidence: 99%